Teknik Dan Metode Penerjemahan Tuturan Ekspresif Bahasa Jepang Dalam Subtitle Film Paradise - Wiguna, I Made Agus Nugraha Arta; Suartini, Ni Nengah; Yuda Pramesti, Putu Dewi Merlyna (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 4 No 1 (2022)DO - 10.24843/JS.2022.v04.i01.p06, 2022)
This study aims to describe the techniques and methods of translating expressive speech act in the subtitle of Paradise Kiss, which was translated by Island Fansubs. To analyze the data of this study using glossing techniques and translational equivalents. Based on the results of the study, it was found that there were 6 types of Japanese expressive speech act. The types of expressive speech act found were then translated using 8 types of translation techniques, amplification, discursive creation, established equivalent, generalization, linguistic amplification, literal translation, particularization and reduction. Expressive speech act translation techniques are dominated by linguistic amplification. Finally, there are 4 types of translation methods, word for word translation, idiomatic translation, free translation and communicative translation. The translation method is dominated by the free translation method.